Constructing the Crime Canon: Dorothy L. Sayers as an Anthologist. Issue 2 (November 2021) - Stewart, Victoria
A consideration of Dorothy L. Sayers's work as an anthologist of short detective fiction during the late 1920s and early 1930s shows how, though hemmed in by considerations of cost and copyright, Sayers used the compiling of anthologies both as a means of promoting her ideas about the detective form and to foster connections with fellow practitioners. An analysis of Sayers's five anthologies shows her favouring particular authors and stories, even while accommodating different audiences and venues of publication. She thus constructed a canon of short detective fiction, one that continues to exert influence on understandings of the form.